A SYSTEMS PHARMACOLOGY MODEL TO EXPLAIN DEVELOPMENTAL DIFFERENCES IN SENSITIVITY TO DRUG-INDUCED QT PROLONGATION. Issue 1 (14th December 2015) - Gotta, Verena; Pfister, Marc; Anker, John van den; Graaf, Piet van der
Abstract : Background: Neonates have been reported to be more sensitive to drugs prolonging the QT-interval than adults. As explanation a developmental change in myocardial ion-channel density has been proposed. Here we explore changes in ion-channel density using a mechanistic pharmacodynamic model and clinical sotalol literature data. Materials and Methods: The applied model relates in vitro and in vivo drug potency (regarding IKr-receptor occupancy and QTc-prolongation, respectively) by a system-specific transducer function. We characterized this function first for preclinical dog and in vitro data (moxifloxacin, sotalol, dofetilide). From a corresponding dofetilide model in adults we derived scaling factors for the system-specific parameters (maximal in vivo QTc-effect Em, dog/Em, adults, transducer ratio τ, dog/τ, adults; τ is proportional to the receptor density in vivo). The derived relationship was used to predict clinical sotalol pharmacodynamics in adults. Literature data was used to evaluate this scaling approach. Simulations of different τ values were performed to explore pharmacodynamic differences in neonates. Results: In adults, the agonistic activity of dofetilide was higher than in dogs (τ, adults≈2x τ, dogs), while the estimated maximal in vivo QTc-prolongation was similar (Em≈27% from baseline). This relationship could also predict clinical sotalol pharmacodynamics in adults and children. The steeper PD profile in neonates could be explained by a higher IKr-receptor density (τ, neonates≈2x τ, adults). Conclusion: This model-based approach allowed to integrate and scale in vitro and in vivo (preclinical, clinical adult and neonate) drug effects on the QTc-interval. The preliminary results confirm the hypothesis that IKr-receptor density is higher (≈2 times) in neonates than in adults and children.